Estimation of Tsunami Hazard and Evacuation Sites using The Cornell Multigrid Couple Tsunami Method in South Button Regency - Ilham, Ilham; Safani, Jamhir; Muliddin, Muliddin; Sulistian, Teguh; Koesuma, Sorja (Department of Physics, Sebelas Maret University, 2025)
The 1992 earthquake and tsunami in the Flores Sea proved that the tsunami impacted the people of the South Buton Region. This research aims to map tsunami hazards and estimate evacuation routes and sites in the South Buton Regency. These evacuation routes and sites are very crucial for disaster preparedness and reducing the risk of tsunami disasters. This research simulates the tsunami wave hazard from the 1992 Flores earthquake using the Cornell multigrid coupled tsunami (COMCOT). We designed the study area in five layers and seven sublayers, encompassing 13 villages on the coast of South Buton Regency. The research generated seven tsunami hazard maps based on the number of existing sublayers, each equipped with evacuation routes and locations. In general, the seven study areas have two tsunami hazard levels: a hazard level with an inundation height of less than 0.5 m and a hazard level with an inundation height of 0.5–3 m. The tsunami inundation distance for the height of 0.5-3 m varies. The shortest inundation distance is 5–33 m in Lakambau and Laompo Villages, while the farthest distance is 57–98 m in Katampe, Lamaninggara, and Molona Villages. Apart from that, the tsunami wave arrived around 35–45 minutes after the earthquake. The fastest arrival time is 35 minutes in Bahari Village, which is closest to the source of the tsunami. The results of the study recommend 17 temporary evacuation sites (TES) and 7 final evacuation sites (FES) in the research area.